The Kinetics of Anti-HLA Antibodies in the First Year after Kidney Transplantation: In Whom and When Should They Be Monitored? - Castro, Maria Cristina Ribeiro de; Barbosa, Erick A.; Souza, Renata P.; Agena, Fabiana; Souza, Patrícia S. de; Maciel, Gabriella; Rodrigues, Hélcio; Panajotopoulos, Nicolas; David, Daísa S.; Paula, Flávio J. de; David-Neto, Elias (Journal of Transplantation, 2018)
The impact of the kinetics of the anti-HLA antibodies after KTx on the occurrence of acute rejection as well as the better time-point to monitor anti-HLA Abs after transplantation is not completely defined. This prospective study followed 150 patients over 12 months after transplantation. Serum IgG anti-HLA Abs were detected by single antigen beads after typing donors and recipients for loci A, B, C, DR, and DQ. Before KTx, 89 patients did not present anti-HLA Abs and 2% developed “de novo” Abs during the 1st year, 39 patients were sensitized without DSAs, and 13% developed DSA after surgery; all of them presented ABMR. Sensitized patients presented higher acute rejection rates (36.4% versus 13.5%, p<0.001), although 60% of the patients did not present ABMR. Patients, in whom DSA-MFI decreased during the first two weeks after surgery, did not develop ABMR. Those who sustained their levels presented a rate of 22% of ABMR. 85% of patients developed ABMR when MFIs increased early after transplantation (which occurred in 30% of the DSA positive patients). In the ABMR group, we observed an iDSA-MFI sharp drop on the fourth day and then an increase between the 7th and 14th POD, which suggests DSA should be monitored at this moment in sensitized patients for better ABMR prediction.